Gestión financiera de la microempresa de productos de primera necesidad 13 14 de la ciudad de Babahoyo - Narváez Livicota, Silvana María (2021)
The need arose to create a micro-business in the May 4 market because we observed that the community wanted to have a variety of basic necessities such as a well-stocked store since the wholesale market needs to supply its customers with a variety of products. The key point of the idea of this business is to improve the service and quality of essential products. We have noticed and observed that the inhabitants of this sector complain about the adulteration of prices, this causes citizens to want to buy their products in neighboring places, although this also generates a little expense, upsetting direct consumers such as the population. that since they have no other alternatives to buy, they have to pay exaggerated prices. Our purpose of creating a pantry in this place very welcomed by the citizens is to later satisfy the needs of the people who live in the sector and so that they do not have to resort to traveling to other distant places in the city in search of better prices. , products in good condition that contain quality and hygiene. Our proposal is to produce greater sources of accessibility to the client in order to achieve the objectives and goals proposed in the execution of the project, cooperate so that every day growth is directly reflected in the population that is our most important human resource, the indicators that will reflect a progressive change in this commercial sector of the community of the citadel May 4, they will be our letter of introduction, providing the best services and quality in the sector